1987
DOI: 10.1090/s0002-9939-1987-0894451-2
|View full text |Cite
|
Sign up to set email alerts
|

Maximal ideals in subalgebras of 𝐶(𝑋)

Abstract: ABSTRACT. Let X be a completely regular space, and let A(X) be a subalgebra of C(X) containing C*{X). We study the maximal ideals in A(X) by associating a filter Z(f) to each / 6 A(X). This association extends to a oneto-one correspondence between M(A) (the set of maximal ideals of A(X)) and ßX. We use the filters Z(f) to characterize the maximal ideals and to describe the intersection of the free maximal ideals in A(X). Finally, we outline some of the applications of our results to compactifications between v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…By an intermediate ring of measurable functions we mean a subring N (X, A) of M(X, A) which contains M * (X, A) of all the bounded measurable functions on X. The main technical tool in this section, which we borrow from the articles [13], [14], [15], is that of local invertibility of measurable functions on measurable sets in the given intermediate ring. With each maximal ideal M in N (X, A), we associate an A-ultrafilter Z N [M ] on X which leads to a bijection between the set of all maximal ideals of N (X, A) and the family of all A-ultrafilters on X (Theorems 4.6 and 4.7).…”
Section: Introductionmentioning
confidence: 99%
“…By an intermediate ring of measurable functions we mean a subring N (X, A) of M(X, A) which contains M * (X, A) of all the bounded measurable functions on X. The main technical tool in this section, which we borrow from the articles [13], [14], [15], is that of local invertibility of measurable functions on measurable sets in the given intermediate ring. With each maximal ideal M in N (X, A), we associate an A-ultrafilter Z N [M ] on X which leads to a bijection between the set of all maximal ideals of N (X, A) and the family of all A-ultrafilters on X (Theorems 4.6 and 4.7).…”
Section: Introductionmentioning
confidence: 99%
“…This gives an answer to the question raised by Redlin and Watson [5]. It has further been shown that a minimal algebra thus obtained need not be minimal with respect to set inclusion, however it still remains open whether such a minimal algebra exists with respect to set inclusion.…”
Section: Redlin and Watsonmentioning
confidence: 62%
“…Redlin and Watson [5] raised the following question: Given a realcompact space X, does there exist in some sense a minimal algebra A m over R for which X is A m -compact? In this section we give an answer to this question.…”
Section: On a Question Raised By Redlin And Watsonmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure space of a commutative ring R with unity stands for the set of all maximal ideals of R equipped with the wellknown hull-kernel topology. It was established in [21] and [22], independently that the structure space of all the intermediate rings of real-valued continuous functions on X are one and the same viz the Stone-Čech compactification βX of X. It follows therefore that the structure space of each intermediate ring of complex-valued continuous functions on X is also βX.…”
Section: Introductionmentioning
confidence: 98%